2016
DOI: 10.1007/s10008-016-3198-3
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical performance of AB3-type hydrogen storage alloy as anode material for the nickel metal hydride accumulators

Abstract: For the purpose of lowering the cost of metal hydride electrode, the La of LaY 2 Ni 9 electrode was replaced by Ce. The electrochemical performances of the CeY 2 Ni 9 negative electrode, at a room and different temperatures, were compared with the parent alloy LaY 2 Ni 9. At room temperature during a long cycling, the evolution of the electrochemical capacity; the diffusivity indicator (H 2 D a), the exchange current density, and the equilibrium potential were determined. At different temperatures, the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 83 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…The hydrogen storage alloy is critical for the hydrogen storage system. Many hydrogen storage alloys had been investigated, including AB 5 , A 2 B 7 , AB 3 , AB, AB 2 , and light metal Mg system alloy . Typically, the AB 5 ‐type alloys are composed of expensive rare earth metal and Ni .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen storage alloy is critical for the hydrogen storage system. Many hydrogen storage alloys had been investigated, including AB 5 , A 2 B 7 , AB 3 , AB, AB 2 , and light metal Mg system alloy . Typically, the AB 5 ‐type alloys are composed of expensive rare earth metal and Ni .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our paper showed that the electrochemistry capacity of the LaGaO 3 oxide can reach 220 mAh g −1 and suggested the possibility of using this oxide as new electrode materials in the Ni‐MH hydrogen batteries at high temperature (328 K) . The literature shows that there is a narrow relationship between temperature and electrochemical properties of hydrogen storage alloys of different kinds …”
Section: Introductionmentioning
confidence: 94%
“…The number of activation cycles is an indication of the compound's performance. 86,87 For the CaNi alloy obtained by a mechanical alloying process for 40 h. They showed that all electrodes are activated during the first activation cycle. 61 Zang et al analyzed the Ca-Mg-Ni mixture where Ca is replaced by Nd, Gd, and Er.…”
Section: During Chargingmentioning
confidence: 99%